Risk Assessment of Hospital Staffs\' Healthcare by MAPO Index Method - Asma BARAZANDEH; Hojatollah KAKAEI (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Non-standard equipment in terms of ergonomics has a substantial influence on increasing musculoskeletal disorders, especially for hospital staffs involved with these problems for patients' displacement. This study was conducted to investigate this vulnerable group. Methods: This descriptive-analytic study was conducted in Imam Khomeini and Mostafa Khomeini hospitals in Ilam in 2012. MAPO Index was used for the study. In this method, several factors including lifting, minor assistance, wheelchair coefficient, etc., are investigated. Data analysis was conducted by SPSS-16 software. Results: Ninety five staffs of Imam Khomeini and Mostafa Khomeini hospitals were selected from 20 sections who were responsible for the patient's displacement. . The maximum displacement was from bed to wheelchair (Imam Khomeini Hospital 67%, Mostafa Khomeini Hospital 61%). The average final number of MAPO index in Imam Khomeini and Mustafa Khomeini Hospitals was 25.2 and 14.4, respectively, which was much higher than normal (0-1.5). Conclusions: In this study, the obtained MAPO index number was in red band which indicates a high risk of back pain due to patients' displacement among the personnel Therefore, short-term and immediate planning of health care, the use of appropriate aids for patients' displacement, and training how to correctly displace patients is required in an ergonomic way.